A systemic functional linguistic investigation of interpersonal meanings in Malay help-seeking and help-providing texts / Dia Widyawati Amat - Dia Widyawati, Amat (2015)
The current study is about a Systemic Functional Linguistic analysis of interpersonal meanings in Malay advice columns. Helper-helpee relationships, judgments and attitudes are identified by looking at the system of Mood and Modality in the advice columns. Many studies investigating English advice column has been found (McCabe, 2005; Asera, Bagarukayo, Shuey &Barton, 1997; Locher, 2006; Kistnasamy, 2006; Jackson, 2005; Gies, 2004; Liao & Liao, 2009; Shaidatul, 2012) but the ones grounded in SFL are still few (Wong, 2009; Zeng, 2009) whereas the study of advice column in Malay language using SFL has not been found. This shows that studying interpersonal meanings in advice columns in Malay from the perspective of SFL is relatively new and deserves studies on its own. Therefore, the current study intends to fill the gap by exploring the Mood and Modality system in Malay advice columns which function as help-seeking and help-providing texts. The current study is a qualitative study (Creswell, 2009) with qualitative and quantitative findings (Silverman, 2006) following the tradition of research in SFL. The data consist of 10 help-seeking texts and 10 help-providing texts which are taken from 10 sets of letters featured in the advice columns of a Malay health magazine, ‘Rapi’. The study was carried out by integrating Halliday’s Mood and Modality theoretical framework (Halliday & Matthiessen, 2004) with Asmah’s (2008) model for Modus and Kata Kerja Modalitas. The findings show that both texts are highly declarative while interrogative and imperative mood are used minimally. Help-seekers use mainly the declarative mood to provide background to their problems while help-providers use mainly the declarative mood to be approachable and to create provocation. As for modality, help-providers use more features of modality than help-seekers to compensate for the lack of authoritativeness caused by indirectness when giving advice.